A comparitive analysis of patterns of recent extinction in birds and mammals - Githiora, Yvonne (Percy FitzPatrick Institute of African Ornithology, 2014)
Exploring past extinction patterns among taxa can inform us about risks facing currently threatened taxa if such extinctions have been non-random with respect to phylogeny and/or geographical patterns. This study analyses patterns of recent extinctions among birds and mammals in order to determine factors influencing these patterns and whether these factors differed between the two groups. Data on bird and mammal species that have become extinct since 1500, including their distributions and body-masses, were collected from diverse sources. GIS mapping was used to determine spatial patterns of species extinctions. The body-mass distributions of extinct species were also compared with body-mass distributions of samples of extant species. Patterns of extinction were found to differ geographically among birds and mammals. However, underlying factors influencing these patterns were found to be similar, with species endemism being an important predictor of recent extinctions. Recently extinct species were larger, on average, than extant species in both birds and mammals pointing to the influence of human over-exploitation in the extinctions. Invasive species, particularly mammals such as rats, were also an important driver, influencing species extinctions by preying on native birds and competing with native mammals of similar biology. These findings can most likely be extrapolated to reptiles, whose extinctions have been similarly influenced by invasive mammals but not necessarily to amphibians whose recent extinctions and declines are being driven primarily by a complex interaction of factors including emerging infectious diseases.